ANALISIS KORELASI ANTARA JUMLAH PENDUDUK DENGAN IMPOR BERAS INDONESIA - Hendri Putranto, Afif; Suwali, Suwali; Sitanini, Ayu; Bintang Panunggul, Victor (Perwira Journal of Economics & Business, 2023)
Indonesia is one of the biggest rice consuming countries in the world. The Indonesian population is very dependent on rice as a staple food. Rice is a staple food that has many problems in stock supply. In order to prevent a food crisis from occurring, the government must pay full attention to providing stock for national consumption needs. Domestic rice production has not been able to meet the needs of national consumption, so the government needs to import rice from outside. The reason why Indonesia has to import rice is the declining number of paddy fields. Many paddy fields that were originally used for rice farming have been converted to other economic activities. The increasingly high population growth is a challenge for the government in meeting the national rice needs. This study aims: (1) To determine the development of rice imports in Indonesia for the period 2011 to 2020. (2) To determine the contribution of rice imports in Indonesia to the availability of national rice stocks for the period 2011 to 2020. This study uses a case study method with a quantitative approach. The data used are secondary data for the period 2011 to 2020, namely the volume of Indonesian rice imports for the period 2011 to 2020, the value of Indonesian rice imports for the period 2011 to 2020 and the volume of domestic rice production for the period 2011 to 2020. The analysis used is descriptive statistical analysis and contribution analysis. rice imports to the national rice stock. The results of the study explain that (1) The development of rice imports in Indonesia for the period 2011 to 2020 is volatile. The average Indonesian rice import is 1,138 235.1 tons per year. The highest rice import occurred in 2011 at 2,750,476 tons. (2) The average contribution of Indonesian rice imports to the national rice stock is 2.5 percent, which is 1,138235.1 tons per year. Most of Indonesia's rice imports come from Vietnam and Thailand